2017
DOI: 10.1177/1744806917729306
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that dry eye represents a chronic overlapping pain condition

Abstract: Recent data suggest that corneal somatosensory dysfunction may be the underlying cause of severe dry eye symptoms in the absence of ocular surface pathology seen in a subset of patients diagnosed with “dry eye syndrome.” This subset of patients tends to demonstrate a unique constellation of symptoms that are persistent, more severe, and generally respond poorly to current dry eye therapies targeting inadequate or dysfunctional tears. A growing body of literature suggests that symptoms in these patients may be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 92 publications
0
35
0
Order By: Relevance
“…But it is relevant that clinicians who care for individuals with these conditions, and who are quite adept at identifying (with blood tests, imaging, or endoscopy) peripheral damage or inflammation, have generally concluded that these are not inflammatory or peripheral‐based disorders. A recent term, Chronic Overlapping Pain Conditions (COPCs), has been coined by the NIH to indicate that FM, IBS, chronic fatigue syndrome (CFS), headache, interstitial cystitis/bladder pain syndrome, TMD, endometriosis, low back pain, and dry‐eye disease may all represent conditions with overlapping clinical and pathophysiological features (i.e., those related to central sensitization), where central factors may be playing a prominent or exclusive role in their pathogenesis (Levitt et al., ; Maixner, Fillingim, Williams, Smith, & Slade, ). Most of the initial studies examining the pathophysiology of central sensitization in humans have been in conditions such as FM and other COPCs, because these were among the first conditions where prominent central factors were identified.…”
Section: Introductionmentioning
confidence: 99%
“…But it is relevant that clinicians who care for individuals with these conditions, and who are quite adept at identifying (with blood tests, imaging, or endoscopy) peripheral damage or inflammation, have generally concluded that these are not inflammatory or peripheral‐based disorders. A recent term, Chronic Overlapping Pain Conditions (COPCs), has been coined by the NIH to indicate that FM, IBS, chronic fatigue syndrome (CFS), headache, interstitial cystitis/bladder pain syndrome, TMD, endometriosis, low back pain, and dry‐eye disease may all represent conditions with overlapping clinical and pathophysiological features (i.e., those related to central sensitization), where central factors may be playing a prominent or exclusive role in their pathogenesis (Levitt et al., ; Maixner, Fillingim, Williams, Smith, & Slade, ). Most of the initial studies examining the pathophysiology of central sensitization in humans have been in conditions such as FM and other COPCs, because these were among the first conditions where prominent central factors were identified.…”
Section: Introductionmentioning
confidence: 99%
“…1 Our understanding of the natural history of persistent pain and the specific environmental and shared genetic factors thought to impact susceptibility to these pain disorders is lacking. 2 Moreover, effective mechanism-based treatments for persistent pain represent a major unmet need in medicine today. Systemic analgesics, including opioids, can be limited by side effects and are inadequate in relieving pain.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, a number of studies have demonstrated strong evidence that these varied disorders: share a strong comorbidity with each other; have similar comorbid symptoms (including sleep problems, fatigue, cognitive slowing); and are associated with objective markers of CS (Harte et al., this Issue; Kindler et al., ; Phillips & Clauw, ; Yunus, 2007b, ). More recently, the National Institute of Health has coined the term Chronic Overlapping Pain Conditions (COPCs) , to categorize these same related disorders (Levitt et al., ; Maixner, Fillingim, Williams, Smith, & Slade, a). It should also be noted that the “ Gate Control Theory of Pain, ” first proposed by Melzack and Wall (), was subsequently extended by Melzack () in proposing the “ Neuromatrix Theory of Pain .” His theory proposed that the experience of pain is a multidimensional process, and is produced by patterns of new impulses generated by a widely‐distributed neural network comprising what he labelled the “body‐self neuromatrix.” This neuromatrix can be modified by sensory experiences and learning, and patterns of nerve impulses can be triggered either by sensory inputs or centrally.…”
Section: Overviewmentioning
confidence: 99%